The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1111/issr.12188
|View full text |Cite
|
Sign up to set email alerts
|

Co‐production and social innovation in street‐level employability services: Lessons from services with lone parents in Scotland

Abstract: The United Kingdom, as an exemplar liberal welfare state, has been characterized as in the vanguard of "work-first" activationdeploying high levels of compulsion and standardized employability services that seek to move people from welfare to work as quickly as possible. However, despite the extension of welfare conditionality to excluded groups such as lone parents, government-led, work-first employability programmes have often proved ineffective at assisting the most vulnerable to escape poverty or even just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Academic reviews of coproduction highlight—with some exceptions32—little critical engagement with issues of power, power relations and representation and whether typical patterns of participation serves to make services more or less inclusive (or do they simply reinforce existing social inequalities?) 9 18.…”
Section: Introductionmentioning
confidence: 99%
“…Academic reviews of coproduction highlight—with some exceptions32—little critical engagement with issues of power, power relations and representation and whether typical patterns of participation serves to make services more or less inclusive (or do they simply reinforce existing social inequalities?) 9 18.…”
Section: Introductionmentioning
confidence: 99%
“…In Scotland, the geographical focus for our research, previous studies identified a strong culture of partnership-working between local government and the third sector that has provided an alternative to contracted-out, work-first activation (Lindsay et al, 2018a). And grant funding provided by charities and nondepartmental public bodies has allowed for innovative local experiments in coproducing high quality employability services (Lindsay et al, 2018c). It is one such innovative initiativeco-producing services with LPsthat provided the context for our research.…”
Section: Co-production As a Route To Personalised Employability Servicesmentioning
confidence: 99%
“…So, co-production promises tailored, personalised services, but crucially sees users as equal partners in shaping those services. There are clear potential benefits for public services and their usersservices may be more tailored to users' needs (Burns, 2013) and more generally better-informed (and therefore potentially of higher quality) because of users' feedback and insights (Pestoff, 2012); users may feel empowered by having a clear influence over the services that they engage with (Verschuere et al, 2012), and may commit more of their 'assets' (in the form of commitment and energy) to making services work (Lindsay et al, 2018b); and their collective engagement and support for services and peer service users may have positive impacts on social capital within targeted communities and groups (Lindsay et al, 2018c). (For further discussion of the concept of co-production, see for example: Burns, 2013;Crompton, 2018;Löffler and Bovaird, 2018).…”
Section: Co-production a S A Route To Personalised Employability Servmentioning
confidence: 99%
“…In an Australian study, Considine et al (2011) showed that quasi‐markets did not meet the expectations of more flexible and personalized service provision, arguing that this is the result of both purchaser and provider behaviour in a market context. In the same vein, Lindsay, Pearson, Batty, Cullen, and Eadson () argue that service provision models built on coproduction rather than contractualization and marketization may provide more opportunities and better conditions for the provision of tailor‐made services and for a more active involvement and participation of jobseekers.…”
Section: Making Welfare Conditional: a Street‐level Perspectivementioning
confidence: 99%